Socioeconomic status and livestock scenario of Spiti valley of Western Himalayas - BISHIST, ROHIT; WANGMO, DEACHEN; GAUTAM, KRISHAN LAL; S, KHALANDAR (The Indian Journal of Animal Sciences, 2022)
Livestock rearing plays a cogent role in the economy of Himachal Pradesh, as it contributes about 28-30% ofthe total value of agricultural produce. In the study area, the majority of livestock farmers belonged to marginalcategory and were rearing sheep, goat, local cattle, Churu and Yak for their sustenance. The literacy rate in the areawas highest in semi-medium farmers followed by small and marginal farmers. Study revealed that contribution oflivestock sector to the gross farmer’s income was highest in case of marginal farmers. In the study area, inadequateexposure to improved breeding practices, scarcity of green fodder and poor marketing facilities were themajor constraints in livestock production. The majority of farmers in this region were adopting modern veterinarymedicines/vaccines for the treatment of their livestock; however, ethnoveterinary practices are still in progress.In the light of results obtained, it can be concluded that the socio-economic status of the livestock farmers in thealpine area of Lahaul and Spiti is appreciable, though there are multiple constraints in livestock production practiceswhich directly affect the animal health and thus the farmers livelihood.